Healthcare assistants' experiences on forensic mental health wards. Issue 3 (22nd January 2018) - Boardman, Stacey; Clarbour, Jane; Rayner, Kelly
Abstract : Purpose: In forensic mental health wards, patients spend more time with healthcare assistants (HCAs) than qualified nurses. Despite this, there is no universally utilised standardised HCA training. The purpose of this paper is to assess the HCAs' experiences in the HCA role in order to better understand how to build on the HCA role to ensure safe practice, and enhance staff well-being. Design/methodology/approach: HCAs working on low and medium secure NHS forensic mental health units were recruited through purposive methods. HCAs engaged in a semi-structured interview, with questions surrounding their support needs, clinical decision making and perception of risks in the role. Template analysis was used, applying an a priori template based on the existing literature to interview transcripts. Findings: The participants described the HCA experience to be defined by two master themes: "HCA factors" and "organisational factors". HCAs valued a holistic patient view which prized patients' experiences. The participants described a lack of role clarity which may be defined through ward expectations and professional experience. Originality/value: HCAs seek a holistic view of the patient; however, some overlooked patient offences in order to do their job. Future research should address how looking past offences impacts security and HCAs' well-being long term.